2021
DOI: 10.3390/fluids6020064
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Aerodynamic Effects of Body Morphing for Passenger Cars in Close-Proximity

Abstract: The potential energy-saving benefit for vehicles when travelling in a ‘platoon’ formation results from the reduction in total aerodynamic drag which may result from the interaction of bluff bodies in close-proximity. Early investigations of platooning, prompted by problems of congestion, had shown the potential for drag reduction but was not pursued. More recently, technologies developed for connected-autonomous vehicle control have provided a renewed interest in platooning particularly within the commercial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The 𝑘 − 𝜀 turbulence model is applied in this CFD simulation because it is feasible for less computational cost and free-shear layer flows with relatively small pressure gradients. Le Good et al, [65], annotated that the 'Resnick model' is created to investigate airflow and aerodynamic of vehicles. This concept adopts of autonomous driving technologies and it is suitable for high-riding coupe/SUV style with full-scale car dimensions of length (L) = 267 mm, height (H) = 98 mm, and width (W) = 108 mm, as shown in Figure 11 [65].…”
Section: Production (Series) Carsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 𝑘 − 𝜀 turbulence model is applied in this CFD simulation because it is feasible for less computational cost and free-shear layer flows with relatively small pressure gradients. Le Good et al, [65], annotated that the 'Resnick model' is created to investigate airflow and aerodynamic of vehicles. This concept adopts of autonomous driving technologies and it is suitable for high-riding coupe/SUV style with full-scale car dimensions of length (L) = 267 mm, height (H) = 98 mm, and width (W) = 108 mm, as shown in Figure 11 [65].…”
Section: Production (Series) Carsmentioning
confidence: 99%
“…Le Good et al, [65], annotated that the 'Resnick model' is created to investigate airflow and aerodynamic of vehicles. This concept adopts of autonomous driving technologies and it is suitable for high-riding coupe/SUV style with full-scale car dimensions of length (L) = 267 mm, height (H) = 98 mm, and width (W) = 108 mm, as shown in Figure 11 [65]. The numerical value for the coefficient drag (𝐶 𝐷 ) is 0.27 with the inlet velocity of 40 m/s.…”
Section: Production (Series) Carsmentioning
confidence: 99%
“…For an individual vehicle within a platoon, its drag is influenced by its geometry and the geometries of those around it leading to optimisation studies for the ordering of vehicles in the platoon. The addition of active aerodynamic devices and body morphing to further enhance the drag reduction has also been investigated [10], but despite our rapidly developing understanding of the flow structures associated with vehicles in very close proximity, it is perhaps surprising to note that published data on long platoons of different vehicle types suggest that the overall energy saving of the platoon is not greatly affected by the ordering of vehicles [11].…”
Section: Introductionmentioning
confidence: 99%
“…For two-vehicle pairs, it has been reported that the effects of geometry and order have a significant effect on their individual and combined aerodynamic drag, so optimisation is essential [10]. Designs for further improving the efficiency of a vehicle pair have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…He then noted that at large spacings between x/L = 1 and 2 that the drag on the bodies become constant as they resumed a flow like that of the isolated body. Papers from Kim and Le Good [14,15] both used simplified bodies to investigate the aerodynamic impact on the geometry of the platoon members and its effects on the drag of the platoon. Also notable is the work that has been done on HVPs by the likes of Watts et al [2] who used CFD studies to analyze the interactions of tractor trailer platooning as well as the flow around surface mounted cubes in a tandem orientation.…”
Section: Introductionmentioning
confidence: 99%